Utilization of Metallurgical Slags in Cu-free Friction Material Formulations - Vlastimil Matějka; Priyadarshini Jayashree; Mara Leonardi; Jozef Vlček; Tomáš Sabovčík; Giovanni Straffelini (Lubricants, 2022)
The aim of our research was to indicate the suitability of metallurgical slags (two blast furnace slags and one steel furnace slag) as the components of Cu-free friction materials. The base mixture consisted of nine components including phenolic resin, graphite, tin sulphide, steel and aramid fibers, iron powder, a mixture of barite with calcite, and vermiculite. To this base mixture, the slags with a particle size below 0.1 mm were added individually in the amount of 20 wt.%. A base friction mixture with alumina in the amount of 20 wt.% represented the reference. Samples for the friction-wear tests were produced in the form of pins by hot press molding. The prepared pins were tested using a pin-on-disc tester in a drag mode at the pressure of 1 MPa and a constant sliding speed of 1.51 m/s for 90 min. The samples with slags exhibited slightly lower values of steady-state friction coefficient compared to the reference composite with alumina, and at the same time produced lower wear particle emissions. The particle concentration was reduced for the samples with slowly cooled blast furnace and steel furnace slag. The results obtained indicated steel furnace slag as a promising component of Cu-free friction composites.